Evidence for compound heterozygosity causing mild and severe forms of autosomal recessive spinal muscular atrophy. Issue 12 (December 1996) - Talbot, K; Rodrigues, N; Bernert, G; Bittner, R; Davies, K
Abstract : Spinal muscular atrophy is an autosomal recessive disease of motor neurone degeneration which shows a variable phenotype. Two candidate genes show deletions in affected subjects but with no distinction between different forms of the disease. We report an unusual family in which mild and severe SMA coexists and patients are deleted for the SMN gene. The father is affected with late onset SMA; therefore this family shows pseudodominant inheritance. When typed using closely linked flanking markers the severely affected son does not share the same haplotype as his sib, who is deleted for SMN but shows no signs yet of SMA. This supports the hypothesis that differences in SMA phenotype can be explained by a multiple allele model.